Impact of Demographic Factors on Consumer’s Purchasing Decision: A Study on the University Students of Peshawar Region - IHSAN ULLAH; SALEEM ULLAH KHAN; MUHAMMAD IDREES (Journal of Business & Tourism, 2021)
This research report is based on the factors affecting the purchasing decision of the students (consumers) of various public and private sector universities in Peshawar (Pakistan). The main objective of this study was to find out the impact of demographic factors such as gender, age and income on consumers purchasing decision. In this study the population was students of various private and public sector universities of Peshawar region. A sample of 250 students was drawn from population through proportionate random sampling technique. A questionnaire was designed and personally distributed among the subjects of sample. Independent samples T-test and ANOVA were used for data analysis. The findings lead to the conclusion that there is no significant relationship between consumers’ gender and age with purchasing decision while income of consumers significantly affects their purchasing decision.